Manganese increases high mannose glycoform on monoclonal antibody expressed in cho when glucose is absent or limiting: implications for use of alternate sugars - Surve, Tanaya; Gadgil, Mugdha (Biotechnology Progress, 2015)
Alternate sugars such as galactose and fructose are metabolized at a slower rate than glucose and result in lower accumulation of lactate. While low lactate accumulation is desirable, we report that complete substitution of glucose with these sugars results in an increase in M5 high mannose glycans. Surprisingly, this increase is much higher when the culture is supplemented with manganese: for example, when cells are cultured with galactose, M5 high mannose glycan content increased from 5% at 1 nM Mn2+ in the basal medium to 32% with 16 mu M Mn2+ supplementation. When galactose is supplemented with glucose maintained at low concentrations, a small reduction in high mannose glycans is seen. In control cultures with glucose, the high mannose content was however <2% in this range of Mn2+ concentration. By varying Mn2+ and glucose supplementation levels, with or without galactose, we systematically demonstrate that Mn2+ concentration and glucose availability, together, significantly affect the high mannose glycan content. To our knowledge, this is the first report that shows that the effect of Mn2+ on high mannose glycan content depends on glucose availability. At each Mn2+ supplementation level evaluated, galactosylation percentages were highest for cultures where galactose was supplemented with glucose at non-limiting concentration. (c) 2014 American Institute of Chemical Engineers Biotechnol. Prog., 31:460-467, 2015
Keywords: CHO; fructose; galactose; glucose; glycosylation; high-mannose glycan; manganese